Adolescent Diet Induce Obesity - Satrianugraha, Muhammad Duddy; Fatmala, Ully Tangziyah; Aziziyah, Qurroti A’yunina (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
BACKGROUND: Obesity results from a long-term imbalance between energy intake and energy expenditure. The 2023 Indonesian Health Survey (SKI) reported an obesity prevalence of 38% in adolescents aged >15 years and 25.7% in adolescents aged >18 years in West Java Province. OBJECTIVE: This study aimed to investigate the relationship between dietary intake and the incidence of obesity among male and female students at SMA Negeri 4 Cirebon. METHODS: This cross-sectional observational analytic study employed purposive sampling to select participants based on dietary intake and obesity. The sample size comprised 56 students at SMA Negeri 4 Cirebon. RESULTS: The findings revealed that 6 (10.7%) students had a dietary intake below the Indonesian Recommended Dietary Allowance (AKG), 16 (28.6%) had a dietary intake meeting the AKG, and 34 (60.7%) had a dietary intake exceeding the AKG. Regarding obesity, 22 (39.3%) students were not obese (BMI < 25), while 34 (60.7%) were obese (BMI > 25). Statistical analysis demonstrated a significant positive correlation between dietary intake and the incidence of obesity. CONCLUSION: The study concludes that higher dietary intake is associated with a greater risk of obesity among male and female students at SMA Negeri 4 Cirebon.